Effect of the use of probiotics, prebiotics and symbiotics in Non-Alcoholic Fatty Liver Disease (Research, Society and Development, 2020)
Introduction: Non-Alcoholic Fatty Liver Disease (NAFLD) is a spectrum of chronic liver diseases, being the more common due to obesity prevalence around the world. In this context, there are studies in the literature that ratify the potential effects of microorganisms against the complications of NAFLD. Objective: This review is designed as a check on probiotics, prebiotics and symbiotics in non-alcoholic fatty liver disease. Methodology: a search of articles published in the database Science Direct, PubMed and Cochrane, using a combination of descriptors registered in the Descriptors in Health Sciences (DeCS): non-alcoholic fatty liver disease; microbiome; nutritional intervention; clinical trial. Fifteen original articles were chosen between the years of 2012 and 2018. Results: Studies that used probiotics, prebiotics and symbiotics in NAFLD showed improvement in some parameters that contribute to disease progression, such as: pro-oxidant enzyme action, reduction of adiposity, inflammation and fibrosis in the liver, regulation of intestinal bacterial flora, among others. If they are probiotic bacteria, studies report that they prevent liver damage, improve visceral fat accumulation and insulin sensitivity. Among the effects of prebiotics, the attenuation of the extension of NAFLD, restoring the intestinal microbiota homeostasis and the function of the intestinal epithelial barrier are outstanding. Symbiotics, in turn, significantly decreased levels of alanine aminotransferase, a marker of liver damage, and serum levels of TNFα and PCR. Final considerations: Therapies directed to the intestinal microbiota have become important tools for the treatment of NAFLD, since there are in the literature experimental reports that highlight a series of benefits through the use of probiotics, prebiotics and symbiotics. However, further studies are needed on this topic.